Mindfulness and Well-being: An Applied Buddhist Approach to Reducing Stress in Modern Life - Bharti, (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
This study explores how Buddhist mindfulness principles can effectively reduce stress and enhance overall well-being in the modern world. By examining the impact of mindfulness practices rooted in Buddhist teachings, the research demonstrates their significant benefits for stress management, emotional regulation, and general health. Through both quantitative and qualitative methods, the study presents evidence that individuals who engaged in mindfulness practices experienced notable reductions in anxiety and depression, improved emotional control, and greater feelings of calm and relaxation. The findings underscore the relevance of Buddhist mindfulness in contemporary society and highlight its potential to support mental health. They also illustrate the practical applications of applied Buddhism in everyday life, particularly for individuals, healthcare professionals, and organizations seeking to improve mental well-being through accessible and holistic approaches. Moreover, this research emphasizes the importance of cultural and spiritual contexts when applying mindfulness techniques. It suggests that a deeper understanding of the Buddhist origins of mindfulness can enrich its application and effectiveness across diverse populations and settings. The study also points to the need for further exploration into the limitations and potential adaptations of Buddhist mindfulness for various contexts. Overall, this study contributes to the growing field of mindfulness-based interventions and supports the integration of applied Buddhist principles into modern health and wellness practices.